2012
DOI: 10.1155/2012/191807
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes during a Deep Inspiration Maneuver Predict Fluid Responsiveness in Spontaneously Breathing Patients

Abstract: Objective. We hypothesized that the hemodynamic response to a deep inspiration maneuver (DIM) indicates fluid responsiveness in spontaneously breathing (SB) patients. Design. Prospective study. Setting. ICU of a general hospital. Patients. Consecutive nonintubated patients without mechanical ventilation, considered for volume expansion (VE). Intervention. We assessed hemodynamic status at baseline and after VE. Measurements and Main Results. We measured radial pulse pressure (PP) using an arterial catheter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Alternatively, one can require the patient to perform a deep inspiration [37] or Valsalva manoeuvre [38]. This is not to say that clinicians should ignore the presence of exaggerated cardiopulmonary interaction in this population.…”
Section: Arterial Side or Stroke Volume Based Methodsmentioning
confidence: 99%
“…Alternatively, one can require the patient to perform a deep inspiration [37] or Valsalva manoeuvre [38]. This is not to say that clinicians should ignore the presence of exaggerated cardiopulmonary interaction in this population.…”
Section: Arterial Side or Stroke Volume Based Methodsmentioning
confidence: 99%
“…Some respiratory interventions have been conducted to improve the predictability of dynamic indices for fluid responsiveness even under spontaneous breathing conditions . Hong et al evaluated whether forced inspiratory breathing could improve the reliability of PPV in predicting fluid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis revealed that PPV during forced inspiratory breathing could predict fluid responsiveness even in the presence of spontaneous breathing, with a high AUC of 0.910. Preau et al found that, in spontaneously breathing patients, the changes in pulse pressure and peak systolic velocity of the femoral artery, induced by a deep inspiration manoeuvre, were significant predictors of fluid responsiveness, with a sensitivity of 90% and a specificity of 100%. Additionally, a previous study conducted by Bronzwaer et al has shown that paced breathing (6 breaths min −1 ) and expiratory resistance increased the power of SPV and PPV for predicting fluid responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations